Prevalence of Halitosis among Orthodontics Patients - Umar Nasir, Sadia Nisar Ahmad, Haris Javed, Ashfaq Ahmad, Syed Mustafa, Maryam Ijaz (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate prevalence and knowledge about halitosis among the patients visiting orthodontic department after application of Orthodontics appliances. Study design: Cross-sectional study Place and duration of study: Department of Orthodontics, Bacha Khan College of Dentistry, Mardan from 1st October 2020 to 30th September 2021. Methodology: A questionnaire based study was carried out on a total of 700 orthodontic patients. Only those patients were included who had orthodontic appliances. Results: 52.30% of the respondents were having prevalence of bad breath. Among those who had prevalence of bad breath, approximately two third (73%) were self-aware of their bad breath. 530 (75.71%) were conscious that they should appointment a dentist while majority were uninformed of the medical term for bad breath i.e. meaning of Halitosis 470 (67.15%). Conclusion: The frequency of halitosis amongst the patients was found to be 52.30%.